PENGARUH KOMUNIKASI KELOMPOK TERHADAP SIKAP IMITASI K-STYLE PADA GRUP CHAT HELLO SHINEE ID: Pendekatan Social Learning Theory - Nur Syamsiah (2021)
This study discusses the effect of group communication on the attitude of K-Style imitation in the Hello Shinee ID chat group. Communication within the group can basically affect its members. One that is influenced is attitude, for example is the attitude of imitation. Nowadays, there are many people who like K-Pop from various circles, both young and adults and also not a few who imitate the style of dress or make up of K-Pop idols. K-Pop idol groups have their own set of fans, the fandom. From the fandom, chat groups emerged that focused on talking about their favorite idol group, one of which was the Hello Shinee ID chat group. The theory in this study uses social learning theory or social learning theory. This study uses quantitative methods and types of explanatory research. The population and sample in this study were members of the Hello Shinee ID chat group. The results of this study found that there was a significant correlation between group communication and K-Style imitation. 23.2% of group communication affects imitation in the Hello Shinee ID chat group, while the remaining 76.8% is caused by other factors that the authors did not examine in this research. Although the members don't really follow the style of the members of the Shinee group, they have a tendency to have items that are the same color as the Shinee fandom color, namely pearl aqua color.